2000
DOI: 10.1177/089686080002000622
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lean Body Mass as a Nutritional Index in Chinese Peritoneal Dialysis Patients—Comparison of Creatinine Kinetics Method and Anthropometric Method

Abstract: Objective To compare, in Chinese continuous ambulatory peritoneal dialysis (CAPD) patients, the creatinine kinetics method (LBM-CK) and the anthropometric method (LBM-AM) for determining lean body mass (LBM). Design Single-center cross-sectional study. Patients and Methods We studied 151 unselected CAPD patients (78 males, 73 females). We calculated LBM-CK and LBM-AM using standard formulas. The results of the two methods were then compared by the Bland and Altman method. Dialysis adequacy and other nutritiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 20 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…Total body water (V) was determined using Watson et al ‘s formula (15). Percentage lean body mass (%LBM) was determined using the creatinine kinetics method, according to Forbes and Bruining (16), that was described in detail in our previous study (17). Serum albumin concentration, %LBM, and nPNA were used as nutritional parameters in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Total body water (V) was determined using Watson et al ‘s formula (15). Percentage lean body mass (%LBM) was determined using the creatinine kinetics method, according to Forbes and Bruining (16), that was described in detail in our previous study (17). Serum albumin concentration, %LBM, and nPNA were used as nutritional parameters in this study.…”
Section: Methodsmentioning
confidence: 99%
“…A significant increase in albumin concentration can occur together with muscle mass depletion. Lean body mass, as determined by creatinine kinetics [ 38 ], anthropometry and bioelectrical impedance, correlated poorly or not at all with serum albumin level [ 39 ]. Megestrol acetate has glucocorticoid-like activity [ 25 , 40 ], and glucocorticoids are known to upregulate albumin gene expression in vitro [ 41 ] and to increase albumin synthesis in vivo [ 42 ], while stimulating muscle protein breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found that lean body mass determined by anthropometric method had poor correlation with that derived from creatinine kinetics and may not be reliable in Chinese. [25] The Bergstrom's formula is now regarded as the ideal method for calculation of PNA. [3,4] Although the DOQI guidelines also recommend the Randerson's formula, [4,5] there are methodological concerns.…”
Section: Discussionmentioning
confidence: 99%